Psychopedagogy in Ibero-America and the Right to Learn According to the Subjective Condition (Educational Knowledge, 2024)
Addressing the theme and issues surrounding the status of Psychopedagogy in Ibero-America and its relationship with the right to learn according to one’s own subjective condition at all stages of life implies adopting an impartial and situated epistemological and methodological standpoint. At early decades of the 21st century, the epistemological condition of Psychopedagogy in Ibero-America is linguistically and epistemologically polysemic, as it designates a science, discipline, and/or profession and qualifies a field and community of practices and expertises scientifically grounded. There is also an impartial process of reconfiguration of the psychopedagogical object: a shift from the pathologization of the subject and homogenization of learning to the psychopedagogical diversity of the subject (individual and/or collective) learning at each stage of life in the different contexts in which it unfolds. Psychopedagogy collaborate with the right to learn according to one’s own subjective condition, through the production of scientific knowledge, and the configuration of specific professional expertise on psychopedagogical diversity.
Keywords: Quantum; Synergy; Resilience; Serendipity; Ethereal